SYNTHESIS AND SPATIAL SIMULATION OF SINGLE T-CODES - Білецький, А. Я.; Кучер, О. Г. (Proceedings of National Aviation University (archive), 2021)
Algorithms for modeling homogeneous codes formed by such complete sequences of t-numbers of length n, in which the Heming distance between any neighboring combinations of codes is equal to a constant value of Y. The question of constructing spatial models of t / p / I codes on a PC are considered.